Novel recombinant material and preparation method thereof

A recombinant material with a sandwich structure using different phenolic resins for the surface and core layers, optimized for low-temperature curing, addresses uneven resin curing in existing methods, enhancing mechanical properties and reducing energy consumption.

CN119188934APending Publication Date: 2024-12-27DYNEA GUANGDONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311852265.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing hot pressing methods for recombinant materials made from wood or bamboo result in uneven resin curing, leading to stress differences, cracking, deformation, and odor issues due to slow heat transfer, which affects appearance and mechanical properties, and are energy inefficient.

Method used

A recombinant material with a sandwich structure comprising a surface layer and a core layer, using different phenolic resins for each, where the core layer is impregnated with a low-temperature curing phenolic resin modified by carbonate and resorcinol, and process parameters are optimized for faster curing and assembly.

Benefits of technology

The solution enables synchronized resin curing, reduces energy consumption, and improves the physical and mechanical properties of the recombinant material while minimizing odor and color issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188934A_ABST
    Figure CN119188934A_ABST
Patent Text Reader

Abstract

The invention provides a novel recombined material and a preparation method thereof, and belongs to the technical field of wood processing. The upper surface layer and the lower surface layer of the novel recombined material are impregnated with phenolic resin A, the core layer is impregnated with phenolic resin B. The recombined units with different thicknesses of the surface layer and the core layer of the novel recombined material are impregnated with different phenolic resin respectively, and the recombined units on the surface layer use high-permeability phenolic resin. Good water resistance and weather resistance of the product are ensured; the core layer recombination unit is made of low-temperature curing phenolic resin, the curing temperature of the low-temperature curing phenolic resin is low, and the performance difference caused by core layer temperature lag due to the fact that the heat transfer speed is low in the wood / bamboo forming process can be overcome. The novel recombinant material prepared by the invention can be molded and processed at a relatively low temperature, and is low in energy consumption, light in product color and low in sourness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood processing, and in particular relates to a new type of recombinant material and a preparation method thereof. Background Art

[0002] Reconstructed materials are boards or square materials made by processing wood or bamboo into wood reconstructed units (wood bundles, fiberized wood veneers, thin veneers) or bamboo reconstructed units (bamboo bundles, fiberized bamboo veneers), impregnating them with resin, and then drying, temperature and humidity control, paving, hot pressing, etc. At present, the hot pressing method is used to prepare reconstructed materials, and the resin used is mainly low molecular weight phenolic resin for impregnation, which needs to be cured and formed under certain temperature conditions.

[0003] Wood and bamboo are poor conductors of heat, usually with a thermal conductivity of 0.04 to 0.4 W / (m·K). Heat conducts slowly in wood and bamboo. During the hot pressing of reconstituted materials, it often takes some time for the temperature to be transferred from the surface to the core. During this process, there is a certain temperature difference between the surface and the core. The greater the thickness, the higher the temperature difference between the surface and the core. According to tests, for 20 mm thick reconstituted materials, the temperature of the core layer often lags behind the surface temperature by 15 to 20 minutes, and for 40 mm thick reconstituted materials, the temperature of the core layer often lags behind the surface temperature by 40 to 60 minutes. In order to fully cure the core layer resin of the reconstructed material, the reconstructed material is usually processed by hot pressing at a temperature of 140-150°C and a time of 90-150 minutes. The surface reconstructed material is subjected to high temperature (140-150°C) and long time (90-150 minutes) heat treatment, and the surface resin will cure before the core resin. When the core resin is completely cured, the surface resin has been over-cured. The curing of the surface and core resins is not synchronized, resulting in stress difference between the surface and core reconstructed materials, causing cracking and deformation of the surface of the reconstructed material. Long-term heat treatment causes the water in the surface wood and bamboo reconstructed units to evaporate, resulting in too low a moisture content in the surface reconstructed material. Long-term heat treatment causes local carbonization of the surface reconstructed material, forming black spots. In addition, long-term heat treatment will further pyrolyze hemicellulose, starch and other substances in the surface wood and bamboo reconstructed units at high temperature, releasing acid substances such as acetic acid, which gives the reconstructed material a certain odor.

[0004] In summary, the existing technology will affect the appearance, physical and mechanical properties of the recombinant material. In addition, the hot pressing time is long, there will be some waste of heat energy, low production efficiency and other problems. Therefore, a new type of recombinant material is urgently needed. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a new type of recombinant material and a preparation method thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A novel recombinant material comprises a surface layer and a core layer, wherein the core layer is located between two surface layers to form a sandwich structure;

[0009] The thickness of the surface layer is 15-40% of the thickness of the novel recombinant material, and the thickness of the core layer is 30-70% of the thickness of the novel recombinant material;

[0010] The adhesive of the surface layer is phenolic resin A, and the adhesive of the core layer is phenolic resin B;

[0011] The phenolic resin A uses formaldehyde and phenol as co-condensation raw materials;

[0012] The phenolic resin B uses phenol, resorcinol and formaldehyde as co-condensation raw materials and carbonate as a modifier.

[0013] Furthermore, the phenolic resin B comprises the following raw materials in parts by weight: 100 parts of phenol, 120-160 parts of formaldehyde aqueous solution, 2-4 parts of catalyst A, 7-10 parts of catalyst B, 3-6 parts of carbonate, 10-30 parts of resorcinol and 1-5 parts of auxiliary agent.

[0014] Furthermore, the catalyst A is one or more of calcium oxide, calcium hydroxide, barium oxide, barium hydroxide, zinc oxide or zinc hydroxide;

[0015] The catalyst B is sodium hydroxide and / or potassium hydroxide;

[0016] The carbonate is one or more of sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate;

[0017] The auxiliary agent is one or more of urea, ethylene urea, thiourea or dicyandiamide.

[0018] Furthermore, the preparation method of the phenolic resin B comprises the following steps:

[0019] The raw materials are weighed by weight, and then resorcinol, catalyst A and part of the formaldehyde aqueous solution (the molar ratio of formaldehyde to resorcinol is 0.5-1.0) are added to a reactor, and the temperature is raised to 50-70°C and kept warm for 1-2 hours to obtain a pre-reaction liquid C. Phenol and the remaining formaldehyde aqueous solution are added to another reactor (the molar ratio of formaldehyde to phenol is 1.5-2.5), and catalyst B is added, and the temperature is raised to 60-80°C and kept warm for 2-3 hours. After the insulation is completed, the temperature is lowered to 30-35°C, and the prepared pre-reaction liquid C is added, and the temperature is raised to 40-60°C and kept warm for 1-2 hours. After the insulation is completed, carbonate and additives are added, and the insulation is continued for 30-60 minutes, and the temperature is cooled to below 30°C to obtain the phenolic resin B.

[0020] Furthermore, the phenolic resin B has a viscosity of 80-250 cps, a solid content of 50-57%, a pH value of 9.5-10.0, and a gel time of 8-11 min at 130°C.

[0021] The core layer of the recombinant material of the present invention is impregnated with a low-temperature curing phenolic resin (phenolic resin B), which uses carbonate and resorcinol as modifiers, and uses a divalent metal alkaline compound and a monovalent metal alkaline compound as catalysts. The low-temperature curing resin is obtained by a specific synthesis process. First, resorcinol and a portion of formaldehyde react under the catalytic action of a divalent metal to obtain a large amount of ortho-substituted resorcinol and formaldehyde reaction intermediates (pre-reaction liquid C), which have very high reactivity with thermosetting phenolic resins, and continue to react with phenolic resins under certain conditions, greatly reducing the curing temperature of the phenolic resin; after the reaction reaches a certain degree, carbonate is added to the resin to participate in the reaction, further reducing the curing temperature of the resin, while ensuring that the resin has good water solubility and stability, and is more suitable for impregnation. The resin has a fast curing speed, a low curing temperature, mild synthetic process conditions, is suitable for the production of recombinant materials, has high bonding strength, and is green and environmentally friendly.

[0022] Furthermore, the phenolic resin A comprises the following raw materials in parts by weight: 100 parts of phenol, 110-150 parts of formaldehyde aqueous solution, 5-8 parts of catalyst and 1-4 parts of auxiliary agent;

[0023] The catalyst is sodium hydroxide and / or potassium hydroxide;

[0024] The auxiliary agent is one or more of urea, ethylene urea, thiourea or dicyandiamide.

[0025] Furthermore, the preparation method of the phenolic resin A comprises the following steps:

[0026] The raw materials are weighed according to weight proportions, and then phenol and formaldehyde aqueous solution are added into an autoclave, a catalyst is added, the temperature is raised to 60-80° C. and kept warm for 3-4 hours, after the heat preservation is completed, the temperature is lowered to 50-60° C., an auxiliary agent is added, the heat preservation is continued for 30-60 minutes, and the temperature is cooled to below 30° C. to obtain the phenolic resin A.

[0027] Furthermore, the phenolic resin A has a viscosity of 50-150 cps, a solid content of 48-55%, a pH value of 9.2-9.7, and a gel time of 11-14 min at 130°C.

[0028] Furthermore, the surface density of the novel recombinant material is 1.15-1.35 g / cm 3 The density of the core layer in the novel recombinant material is 0.65-1.25 g / cm 3Preferably, the density of the core layer is 0.85-1.15 g / cm 3 .

[0029] The second technical solution of the present invention:

[0030] A method for preparing the novel recombinant material comprises the following steps:

[0031] The surface layer recombinant unit is impregnated or rolled with phenolic resin A to obtain a sizing surface layer recombinant unit, and the core layer recombinant unit is impregnated or rolled with phenolic resin B to obtain a sizing core layer recombinant unit. The sizing surface layer recombinant unit and the sizing core layer recombinant unit are dried, assembled, and hot-pressed to obtain the novel recombinant material.

[0032] Furthermore, the sizing amount of phenolic resin A in the surface layer recombinant unit is 8-25%, the sizing amount of phenolic resin B in the core layer recombinant unit is 5-20%, and the sizing amount of the surface layer recombinant unit is greater than that of the core layer recombinant unit;

[0033] The average fiber bundle diameter of the surface layer reorganization unit is ≤2.5mm, the maximum diameter is ≤3.0mm, and the moisture content of the fiber bundle is 15-25%; the average fiber bundle diameter of the core layer reorganization unit is ≤3.5mm, the maximum diameter is ≤4.5mm, and the moisture content of the fiber bundle is 8-15%.

[0034] Furthermore, during assembly, the mass ratio of the glue surface layer recombinant unit to the glue core layer recombinant unit is 1:2-2:1.

[0035] Furthermore, the hot pressing temperature is 120-140° C., the hot pressing time is 30-150 min, and the hot pressing pressure is 5-15 MPa.

[0036] More specifically, the method for preparing the novel recombinant material comprises the following steps:

[0037] (1) Synthesis of phenolic resin A and phenolic resin B

[0038] (2) Preparation of recombinant units

[0039] Preparation of surface recombinant units: bamboo or wood is deflaked into wood or bamboo recombinant units with an average fiber bundle diameter of ≤2.5 mm and a maximum fiber bundle diameter of ≤3.0 mm using a special deflaking device;

[0040] Preparation of core layer recombinant units: bamboo or wood is deflaked into wood or bamboo recombinant units with an average fiber bundle diameter of ≤3.5 mm and a maximum fiber bundle diameter of ≤4.5 mm using a special deflaking device;

[0041] (3) Primary drying of the reorganization unit

[0042] The prepared surface layer recombinant unit is dried by drying equipment to a moisture content of 3-8% at a drying temperature of 90-110°C; the prepared core layer recombinant unit is dried by drying equipment to a moisture content of 3-8% at a drying temperature of 90-110°C;

[0043] (4) Recombination unit sizing

[0044] The surface reorganization unit after the primary drying is impregnated or rolled with phenolic resin A to obtain a sizing surface reorganization unit, and the sizing amount is 8-25%; the core reorganization unit after the primary drying is impregnated or rolled with phenolic resin B to obtain a sizing core reorganization unit, and the sizing amount is 5-20%;

[0045] (5) Secondary drying of the recombination unit

[0046] The prepared glue surface layer recombinant unit is dried by drying equipment to a moisture content of 15-25% and a drying temperature of 55-65°C; the prepared glue core layer recombinant unit is dried by drying equipment to a moisture content of 8-15% and a drying temperature of 55-75°C;

[0047] (6) Recombination unit balance processing

[0048] The surface reorganization units after secondary drying are subjected to balancing treatment in a balancing room or storage bin until the moisture content is 15-25%, and the moisture content deviation between the surface reorganization units is controlled within 5%;

[0049] The core layer reorganization unit after secondary drying is subjected to balancing treatment in a balancing room or storage bin to a moisture content of 8-15%, and the moisture content deviation between the core layer reorganization units is controlled within 5%;

[0050] (7) Recombination unit assembly

[0051] The mass ratio of the surface layer recombinant unit to the core layer recombinant unit is 1:2-2:1;

[0052] The secondary dried surface reorganization unit is evenly divided into two parts, one of which is laid flat on the laying table along the grain as the lower surface layer, and the secondary dried core layer reorganization unit is laid flat on the lower surface layer reorganization unit along the grain, and then the other secondary dried surface layer reorganization unit is laid flat on the core layer reorganization unit along the grain to complete the assembly;

[0053] (8) Hot pressing of reconstituted materials

[0054] The paved recombinant material slab is sent to a hot press for hot pressing molding. The molding process is as follows: hot pressing temperature 120-140°C, hot pressing time 30-150min, hot pressing pressure 5-15Mpa, and the novel recombinant material can be obtained.

[0055] Compared with the prior art, the present invention has the following advantages and technical effects:

[0056] The surface layer and core layer bamboo units of the novel recombinant material of the present invention are treated with different phenolic resins respectively. The surface layer recombinant unit uses high permeability phenolic resin to ensure that the product has good water resistance and weather resistance; the core layer recombinant unit uses low temperature curing phenolic resin, which has a low curing temperature and can overcome the performance difference caused by the core layer temperature lag caused by slow heat transfer during the molding process of the bamboo recombinant material. The novel recombinant material prepared by the present invention can be molded at a relatively low temperature, has low energy consumption, and the product has a light color and low sour taste.

[0057] The novel recombinant material of the present invention adopts recombinant units with fiber bundles of different diameters, different sizing amounts, and different moisture contents, and is assisted by the setting of process parameters such as hot pressing temperature and hot pressing time to form a sandwich structure with a surface layer density higher than a core layer, thereby improving the physical and mechanical properties of the recombinant material. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0059] Figure 1 It is a schematic diagram of the structure of the novel recombinant material of the present invention;

[0060] Figure 2 Schematic diagram of the height misalignment of the bonding interface between the surface layer recombinant unit and the core layer recombinant unit of the new recombinant material in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0062] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0063] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0064] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0065] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0066] The embodiment of the present invention provides a novel recombinant material, comprising an upper surface layer, a lower surface layer and a core layer stacked in sequence (see the structural schematic diagram Figure 1 , forming a sandwich structure), the thickness of the surface layer is 15-40% of the thickness of the new recombinant material, and the thickness of the core layer is 30-70% of the thickness of the new recombinant material;

[0067] The adhesive of the surface layer is phenolic resin A, and the adhesive of the core layer is phenolic resin B;

[0068] The phenolic resin A uses formaldehyde and phenol as co-condensation raw materials;

[0069] The phenolic resin B uses phenol, resorcinol and formaldehyde as co-condensation raw materials and carbonate as a modifier.

[0070] In an embodiment of the present invention, the phenolic resin B comprises the following raw materials in parts by weight: 100 parts of phenol, 120-160 parts of formaldehyde aqueous solution, 2-4 parts of catalyst A, 7-10 parts of catalyst B, 3-6 parts of carbonate, 10-30 parts of resorcinol and 1-5 parts of auxiliary agent.

[0071] More specifically, the catalyst A is one or more of calcium oxide, calcium hydroxide, barium oxide, barium hydroxide, zinc oxide or zinc hydroxide;

[0072] The catalyst B is sodium hydroxide and / or potassium hydroxide;

[0073] The carbonate is one or more of sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate;

[0074] The auxiliary agent is one or more of urea, ethylene urea, thiourea or dicyandiamide.

[0075] In an embodiment of the present invention, the preparation method of the phenolic resin B comprises the following steps:

[0076] Weigh the raw materials by weight, then add resorcinol, catalyst A and part of the formaldehyde aqueous solution (the molar ratio of formaldehyde to resorcinol is 0.5-1.0) into the reactor, heat it to 50-70°C and keep it for 1-2 hours to obtain a pre-reaction liquid C, add phenol and the remaining formaldehyde aqueous solution into another reactor (the molar ratio of formaldehyde to phenol is 1.5-2.5), add catalyst B, heat it to 60-80°C and keep it for 2-3 hours, and the insulation ends. , lower the temperature to 30-35°C, add the prepared pre-reaction solution C, raise the temperature to 40-60°C, keep warm for 1-2 hours, add carbonate and additives, continue to keep warm for 30-60 minutes, cool to below 30°C, and obtain the phenolic resin B. The phenolic resin B has a viscosity of 80-250cps, a solid content of 50-57%, a pH value of 9.5-10.0, and a gel time of 8-11min at 130°C.

[0077] In an embodiment of the present invention, the phenolic resin A comprises the following raw materials in parts by weight: 100 parts of phenol, 110-150 parts of formaldehyde aqueous solution, 5-8 parts of catalyst and 1-4 parts of auxiliary agent;

[0078] The catalyst is sodium hydroxide and / or potassium hydroxide;

[0079] The auxiliary agent is one or more of urea, ethylene urea, thiourea or dicyandiamide.

[0080] In an embodiment of the present invention, the preparation method of the phenolic resin A comprises the following steps:

[0081] The raw materials are weighed according to weight proportions, and then phenol and formaldehyde aqueous solution are added into an autoclave, a catalyst is added, the temperature is raised to 60-80° C. and kept warm for 3-4 hours, after the heat preservation is finished, the temperature is lowered to 50-60° C., an auxiliary agent is added, the heat preservation is continued for 30-60 minutes, and the temperature is cooled to below 30° C. to obtain the phenolic resin A, wherein the phenolic resin A has a viscosity of 50-150 cps, a solid content of 48-55%, a pH value of 9.2-9.7, and a gel time of 11-14 minutes at 130° C.

[0082] In the embodiment of the present invention, the density of the surface layer of the novel recombinant material is 1.15-1.35 g / cm 3 The density of the core layer in the novel recombinant material is 0.65-1.25 g / cm 3Preferably, the density of the core layer is 0.85-1.15 g / cm 3 .

[0083] The present invention also provides a method for preparing the novel recombinant material, comprising the following steps:

[0084] The surface layer recombinant unit is impregnated or rolled with phenolic resin A to obtain a sizing surface layer recombinant unit, and the core layer recombinant unit is impregnated or rolled with phenolic resin B to obtain a sizing core layer recombinant unit. The sizing surface layer recombinant unit and the sizing core layer recombinant unit are dried, assembled, and hot-pressed to obtain the novel recombinant material.

[0085] In an embodiment of the present invention, the sizing amount of phenolic resin A in the surface layer reorganization unit is 8-25%, and the sizing amount of phenolic resin B in the core layer reorganization unit is 5-20%; the average diameter of the fiber bundle of the surface layer reorganization unit is ≤2.5mm, the maximum diameter is ≤3.0mm, and the moisture content of the fiber bundle is 15-25%; the average diameter of the fiber bundle of the core layer reorganization unit is ≤3.5mm, the maximum diameter is ≤4.5mm, and the moisture content of the fiber bundle is 8-15%.

[0086] In the embodiment of the present invention, the sizing amount of the phenolic resin A in the surface layer recombinant unit is 8-25%, and the sizing amount of the phenolic resin B in the core layer recombinant unit is 5-20%.

[0087] In an embodiment of the present invention, during assembly, the mass ratio of the glue surface layer recombinant unit to the glue core layer recombinant unit is 1:2-2:1.

[0088] In the embodiment of the present invention, the hot pressing temperature is 120-140° C., the hot pressing time is 30-150 min, and the hot pressing pressure is 5-15 MPa.

[0089] All raw materials used in the examples of the present invention are commercially available.

[0090] Unless otherwise specified, the “parts” used in the embodiments of the present invention are “parts by weight”.

[0091] The technical solution of the present invention is further illustrated by the following embodiments.

[0092] The mass concentration of the formaldehyde aqueous solution described in the following examples is 50%.

[0093] Example 1 New bamboo recombinant material

[0094] The novel bamboo reconstructed material of the embodiment of the present invention comprises an upper surface layer, a lower surface layer and a core layer, and the surface layer density of the reconstructed material is 1.35 g / cm 3 , adhesive is phenolic resin A; core layer density is 1.15g / cm 3, the adhesive is phenolic resin B; the thickness of the upper and lower surface layers is 5 mm, the thickness of the core layer is 15 mm, and the height of the dislocation between the surface layer reorganization unit and the core layer reorganization unit at the bonding interface is h (such as Figure 2 The average diameter of the fiber bundle of the surface layer reorganization unit is 2.0 mm, and the maximum diameter is 3.0 mm; the average diameter of the fiber bundle of the core layer reorganization unit is 3.0 mm, and the maximum diameter is 4.5 mm. The core layer is located between the upper and lower surface layers to form a sandwich structure. The specific preparation method is as follows:

[0095] (1) Synthesis of phenolic resin A and phenolic resin B

[0096] Synthesis of phenolic resin A: 100 parts of phenol, 130 parts of formaldehyde aqueous solution, 6.5 parts of catalyst (sodium hydroxide) and 3.5 parts of auxiliary agent (urea) were weighed by weight, and then the phenol and formaldehyde aqueous solution were added into an autoclave, and the catalyst was added, and the temperature was raised to 70° C. and kept warm for 3.5 hours. After the insulation was completed, the temperature was lowered to 55° C., and the auxiliary agent was added. The temperature was kept warm for 45 minutes, and the temperature was cooled to below 30° C. to obtain phenolic resin A. The prepared phenolic resin A had a viscosity of 70 cps, a solid content of 52%, a pH value of 9.60, and a gel time of 12.0 min at 130° C.;

[0097] Synthesis of phenolic resin B: 100 parts of phenol, 140 parts of formaldehyde aqueous solution, 3 parts of catalyst A (calcium oxide), 8 parts of catalyst B (sodium hydroxide), 4 parts of carbonate (sodium carbonate), 20 parts of resorcinol and 2 parts of auxiliary agent (urea) were weighed by weight, and then resorcinol, catalyst A and part of the formaldehyde aqueous solution (10 parts) were added to a reactor, and the temperature was raised to 60°C and kept for 1.5 hours to obtain a pre-reaction liquid C, and phenol and the remaining formaldehyde aqueous solution were added to another reactor ( 130 parts), and catalyst B was added, the temperature was raised to 70°C and kept warm for 2.5 hours, after the heat preservation was completed, the temperature was lowered to 30°C, the prepared pre-reaction solution C was added, the temperature was raised to 50°C, and the temperature was kept warm for 2 hours, after the heat preservation was completed, carbonate and auxiliary agents were added, and the temperature was kept warm for 45 minutes, and the mixture was cooled to below 30°C to obtain phenolic resin B. The prepared phenolic resin B had a viscosity of 110 cps, a solid content of 54%, a pH value of 9.80, and a gel time of 8.9 min at 130°C;

[0098] (2) Preparation of recombinant units

[0099] Preparation of surface recombinant units: bamboo materials are decomposed into bamboo recombinant units with an average fiber bundle diameter of 2.0 mm and a maximum fiber bundle diameter of 3.0 mm using a special decomposition device;

[0100] Preparation of core layer recombinant units: bamboo materials are decomposed into bamboo recombinant units with an average fiber bundle diameter of 3.0 mm and a maximum fiber bundle diameter of 4.5 mm using a special decomposition device;

[0101] (3) Primary drying of the reorganization unit

[0102] The prepared surface layer recombinant unit is dried by a drying device until the moisture content is 8% and the drying temperature is 90°C; the prepared core layer recombinant unit is dried by a drying device until the moisture content is 8% and the drying temperature is 90°C;

[0103] (4) Recombination unit sizing

[0104] The surface reorganized unit after the primary drying is impregnated with phenolic resin A, and the sizing amount is 25%; the core reorganized unit after the primary drying is impregnated with phenolic resin B, and the sizing amount is 12%;

[0105] (5) Secondary drying of the recombination unit

[0106] The pre-impregnated surface layer reorganization unit prepared in step (4) is dried by a drying device until the moisture content is 25% and the drying temperature is 55° C.; the pre-impregnated core layer reorganization unit prepared in step (4) is dried by a drying device until the moisture content is 12% and the drying temperature is 55° C.;

[0107] (6) Recombination unit balance processing

[0108] The surface reorganization units after secondary drying are subjected to balancing treatment in a balancing room until the moisture content is 25%, and the moisture content deviation between the surface reorganization units is controlled within 5%;

[0109] The core layer reorganization unit after secondary drying is subjected to balancing treatment in a balancing room until the moisture content is 12%, and the moisture content deviation between the core layer reorganization units is controlled within 5%;

[0110] (7) Recombination unit assembly

[0111] The mass ratio of the surface layer recombinant unit to the core layer recombinant unit is 0.75;

[0112] The secondary dried surface reorganization unit is evenly divided into two parts, one of which is laid flat on the laying table along the grain as the lower surface layer, and the secondary dried core layer reorganization unit is laid flat on the lower surface layer reorganization unit along the grain, and then the other secondary dried surface layer reorganization unit is laid flat on the core layer reorganization unit along the grain to complete the assembly;

[0113] (8) Hot pressing of reconstituted materials

[0114] The laid reconstructed material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 140°C, hot pressing time 45 minutes, hot pressing pressure 10MPa, and a new type of bamboo reconstructed material can be obtained.

[0115] Comparative Example 1

[0116] The preparation of phenolic resin B was omitted, and the surface recombinant unit after one drying was impregnated with phenolic resin A with a sizing amount of 25%; the core recombinant unit after one drying was impregnated with phenolic resin A with a sizing amount of 12%. Other process parameters were the same as those in Example 1.

[0117] Comparative Example 2

[0118] The preparation of phenolic resin A was omitted, and the surface recombinant unit after primary drying was impregnated with phenolic resin B with a sizing amount of 25%; the core recombinant unit after primary drying was impregnated with phenolic resin B with a sizing amount of 12%. Other process parameters were the same as those in Example 1.

[0119] Comparative Example 3

[0120] Same as Example 1, except that the density of the surface layer and the core layer in the recombinant material is 1.23 g / cm 3 .

[0121] Comparative Example 4

[0122] The same as Example 1, except that the fiber bundles of the surface layer and core layer recombinant units have an average diameter of 3 mm and a maximum diameter of 4.0 mm.

[0123] Comparative Example 5

[0124] The same as Example 1, except that the surface layer recombinant unit after primary drying is impregnated with phenolic resin A, and the sizing amount is 12%; the core layer recombinant unit after primary drying is impregnated with phenolic resin B, and the sizing amount is 12%.

[0125] Comparative Example 6

[0126] The same as Example 1, except that the addition of carbonate (sodium carbonate) is omitted in the synthesis process of phenolic resin B.

[0127] Comparative Example 7

[0128] The same as Example 1, the only difference is that in step (8), the laid reconstituted material slab is sent to a hot press for hot pressing, and the molding process is: hot pressing temperature 160°C, hot pressing time 45 minutes, hot pressing pressure 25 MPa.

[0129] The performance tests were conducted on the novel bamboo recombinant materials prepared in Example 1 and Comparative Examples 1 to 7. The test results are shown in Table 1, wherein the performance test standards are as follows:

[0130] Elastic modulus: measured in accordance with GB / T 17657-2022;

[0131] Static bending strength: measured in accordance with GB / T 17657-2022;

[0132] Horizontal shear strength: measured in accordance with GB / T 30364-2013;

[0133] Water absorption thickness expansion rate: measured in accordance with GB / T 30364-2013.

[0134] Table 1 Performance of bamboo reconstituted materials prepared in Example 1 and Comparative Examples 1 to 7

[0135]

[0136]

[0137] As can be seen from Table 1, the physical and mechanical properties of the reconstructed bamboo material prepared in Example 1 can meet the physical and mechanical performance indicators of "Reconstructed Bamboo Flooring" GB / T 30364-2013, and its comprehensive performance is better than that of the reconstructed bamboo materials prepared in Comparative Examples 1 to 7.

[0138] Example 2 New Poplar Wood Recombinant Material

[0139] The novel poplar wood reconstructed material of the embodiment of the present invention comprises an upper surface layer, a lower surface layer and a core layer, and the surface layer density of the reconstructed material is 1.15 g / cm 3 , the adhesive is phenolic resin A, the core layer density is 0.65g / cm 3 , the adhesive is phenolic resin B, the thickness of the upper and lower surface layers is 5 mm, the thickness of the core layer is 10 mm, the dislocation height h of the surface layer reorganization unit and the core layer reorganization unit at the bonding interface is 2.0 mm, the average diameter of the fiber bundle of the surface layer reorganization unit is 1.5 mm, and the maximum diameter is 2.5 mm; the average diameter of the fiber bundle of the core layer reorganization unit is 2.0 mm, and the maximum diameter is 2.5 mm. The core layer is located between the upper and lower surface layers to form a sandwich structure. The specific preparation method is as follows:

[0140] (1) Synthesis of phenolic resin A and phenolic resin B

[0141] Synthesis of phenolic resin A: 100 parts of phenol, 110 parts of formaldehyde aqueous solution, 5 parts of catalyst (sodium hydroxide) and 1 part of auxiliary agent (thiourea) were weighed by weight, and then the phenol and formaldehyde aqueous solution were added into an autoclave, and the catalyst was added, and the temperature was raised to 80° C. and kept warm for 3 hours. After the insulation was completed, the temperature was lowered to 50° C., and the auxiliary agent was added. The temperature was kept warm for 30 minutes, and the temperature was cooled to below 30° C. to obtain phenolic resin A. The prepared phenolic resin A had a viscosity of 50 cps, a solid content of 48%, a pH value of 9.30, and a gel time of 130° C. of 13.9 min.

[0142] Synthesis of phenolic resin B: 100 parts of phenol, 120 parts of formaldehyde aqueous solution, 2 parts of catalyst A (barium hydroxide), 7 parts of catalyst B (sodium hydroxide), 3 parts of carbonate (sodium carbonate), 10 parts of resorcinol and 1 part of auxiliary agent (thiourea) were weighed by weight, and then resorcinol, catalyst A and part of the formaldehyde aqueous solution (4 parts) were added to a reactor, and the temperature was raised to 70°C and kept for 1 hour to obtain a pre-reaction liquid C, and phenol and the remaining formaldehyde aqueous solution (116 parts) were added to another reactor. A reaction kettle was prepared, and catalyst B was added, the temperature was raised to 80°C and kept warm for 2 hours. After the heat preservation was completed, the temperature was lowered to 35°C, the prepared pre-reaction liquid C was added, the temperature was raised to 60°C and kept warm for 1 hour. After the heat preservation was completed, carbonate and additives were added, and the temperature was kept warm for 60 minutes. The phenolic resin B was obtained after cooling to below 30°C. The prepared phenolic resin B had a viscosity of 230 cps, a solid content of 57%, a pH of 9.50, and a gel time of 10.8 min at 130°C.

[0143] (2) Preparation of recombinant units

[0144] Preparation of surface recombinant units: Poplar wood is decomposed into wood recombinant units with an average fiber bundle diameter of 1.5 mm and a maximum fiber bundle diameter of 2.5 mm using a special decomposition device;

[0145] Preparation of core layer recombinant units: Poplar wood is deflaked into wood recombinant units with an average fiber bundle diameter of 2.0 mm and a maximum fiber bundle diameter of 2.5 mm using a special deflaking device;

[0146] (3) Primary drying of the reorganization unit

[0147] The prepared surface layer recombinant unit is dried by a drying device to a moisture content of 5.0% at a drying temperature of 110°C; the prepared core layer recombinant unit is dried by a drying device to a moisture content of 5.0% at a drying temperature of 110°C;

[0148] (4) Recombination unit sizing

[0149] The surface reorganized unit after the primary drying is impregnated with phenolic resin A, and the sizing amount is 25%; the core reorganized unit after the primary drying is impregnated with phenolic resin B, and the sizing amount is 12%;

[0150] (5) Secondary drying of the recombination unit

[0151] The pre-impregnated surface layer reorganization unit prepared in step (4) is dried by a drying device to a moisture content of 15% at a drying temperature of 65° C.; the pre-impregnated core layer reorganization unit prepared in step (4) is dried by a drying device to a moisture content of 8% at a drying temperature of 65° C.;

[0152] (6) Recombination unit balance processing

[0153] The surface reorganization units after secondary drying are subjected to balancing treatment in a balancing room until the moisture content is 15%, and the moisture content deviation between the surface reorganization units is controlled within 5%;

[0154] The core layer reorganization unit after secondary drying is subjected to balancing treatment in a balancing room until the moisture content is 8%, and the moisture content deviation between the core layer reorganization units is controlled within 5%;

[0155] (7) Recombination unit assembly

[0156] The mass ratio of the surface layer recombinant unit to the core layer recombinant unit is 1.75;

[0157] The secondary dried surface reorganization unit is evenly divided into two parts, one of which is laid flat on the laying table along the grain as the lower surface layer, and the secondary dried core layer reorganization unit is laid flat on the lower surface layer reorganization unit along the grain, and then the other secondary dried surface layer reorganization unit is laid flat on the core layer reorganization unit along the grain to complete the assembly;

[0158] (8) Hot pressing of reconstituted materials

[0159] The laid reconstructed material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 140°C, hot pressing time 30 minutes, hot pressing pressure 5MPa, and a new type of poplar wood reconstructed material can be obtained.

[0160] Example 3 New eucalyptus recombinant material

[0161] The novel eucalyptus wood reconstituted material of the embodiment of the present invention comprises an upper surface layer, a lower surface layer and a core layer, and the surface layer density of the reconstituted material is 1.35 g / cm 3 , the adhesive is phenolic resin A, the core layer density is 0.85g / cm 3 , the adhesive is phenolic resin B, the thickness of the upper and lower surface layers is 5 mm, the thickness of the core layer is 20 mm, the dislocation height h of the surface layer reorganization unit and the core layer reorganization unit at the bonding interface is 4.5 mm, the average diameter of the fiber bundle of the surface layer reorganization unit is 1.5 mm, and the maximum diameter is 2.5 mm; the average diameter of the fiber bundle of the core layer reorganization unit is 3.5 mm, and the maximum diameter is 4.5 mm. The core layer is located between the upper and lower surface layers to form a sandwich structure. The specific preparation method is as follows:

[0162] (1) Synthesis of phenolic resin A and phenolic resin B

[0163] Synthesis of phenolic resin A: 100 parts of phenol, 150 parts of formaldehyde aqueous solution, 8 parts of catalyst (potassium hydroxide) and 4 parts of auxiliary agent (dicyandiamide) were weighed by weight, and then the phenol and formaldehyde aqueous solution were added into a reaction kettle, and the catalyst was added, and the temperature was raised to 60° C. and kept warm for 4 hours. After the insulation was completed, the temperature was lowered to 50° C., and the auxiliary agent was added. The temperature was kept warm for 60 minutes, and the temperature was cooled to below 30° C. to obtain phenolic resin A. The prepared phenolic resin A had a viscosity of 150 cps, a solid content of 55%, a pH value of 9.70, and a gel time of 11.2 min at 130° C.;

[0164] Synthesis of phenolic resin B: 100 parts of phenol, 160 parts of formaldehyde aqueous solution, 4 parts of catalyst A (zinc hydroxide), 10 parts of catalyst B (potassium hydroxide), 6 parts of carbonate (sodium carbonate), 30 parts of resorcinol and 5 parts of auxiliary agent (dicyandiamide) were weighed by weight, and then resorcinol, catalyst A and part of the formaldehyde aqueous solution (10 parts) were added to a reactor, and the temperature was raised to 50°C and kept for 2 hours to obtain a pre-reaction liquid C, and phenol and the remaining formaldehyde aqueous solution were added to another reactor. The mixture was stirred for 3 hours at 60 ° C., and the temperature was lowered to 33 ° C. The prepared pre-reaction solution C was added, and the temperature was raised to 40 ° C. and the temperature was kept for 2 hours. After the temperature was raised, carbonate and auxiliary agents were added, and the temperature was kept for 30 minutes. The mixture was cooled to below 30 ° C. to obtain phenolic resin B. The prepared phenolic resin B had a viscosity of 80 cps, a solid content of 50%, a pH of 10.0, and a gel time of 8.1 min at 130 ° C.

[0165] (2) Preparation of recombinant units

[0166] Preparation of surface recombinant units: Eucalyptus wood is deflaked into wood recombinant units with an average fiber bundle diameter of 1.5 mm and a maximum fiber bundle diameter of 2.5 mm using a special deflaking device;

[0167] Preparation of core layer recombinant units: Eucalyptus wood is deflaked into wood recombinant units with an average fiber bundle diameter of 3.5 mm and a maximum fiber bundle diameter of 4.5 mm using a special deflaking device;

[0168] (3) Primary drying of the reorganization unit

[0169] The prepared surface layer recombinant unit is dried by a drying device until the moisture content is 3.0% and the drying temperature is 100°C; the prepared core layer recombinant unit is dried by a drying device until the moisture content is 3.0% and the drying temperature is 100°C;

[0170] (4) Recombination unit sizing

[0171] The surface reorganized unit after primary drying is impregnated with phenolic resin A, and the sizing amount is 25%; the core reorganized unit after primary drying is impregnated with phenolic resin B, and the sizing amount is 8%;

[0172] (5) Secondary drying of the recombination unit

[0173] The pre-impregnated surface layer reorganization unit prepared in step (4) is dried by a drying device to a moisture content of 25% at a drying temperature of 65° C.; the pre-impregnated core layer reorganization unit prepared in step (4) is dried by a drying device to a moisture content of 6% at a drying temperature of 65° C.;

[0174] (6) Recombination unit balance processing

[0175] The surface reorganization units after secondary drying are subjected to balancing treatment in a balancing room until the moisture content is 25%, and the moisture content deviation between the surface reorganization units is controlled within 5%;

[0176] The core layer reorganization unit after secondary drying is subjected to balancing treatment in a balancing room until the moisture content is 6%, and the moisture content deviation between the core layer reorganization units is controlled within 5%;

[0177] (7) Recombination unit assembly

[0178] The mass ratio of the surface layer recombinant unit to the core layer recombinant unit is 0.80;

[0179] The secondary dried surface reorganization unit is evenly divided into two parts, one of which is laid flat on the laying table along the grain as the lower surface layer, and the secondary dried core layer reorganization unit is laid flat on the lower surface layer reorganization unit along the grain, and then the other secondary dried surface layer reorganization unit is laid flat on the core layer reorganization unit along the grain to complete the assembly;

[0180] (8) Hot pressing of reconstituted materials

[0181] The laid reconstructed material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 140°C, hot pressing time 60 minutes, hot pressing pressure 15MPa, and a new type of eucalyptus reconstructed material can be obtained.

[0182] Example 4 New Rubber Wood Reconstructed Material

[0183] The novel rubber wood reconstituted material of the embodiment of the present invention comprises an upper surface layer, a lower surface layer and a core layer, and the surface layer density is 1.25 g / cm 3 , the adhesive is phenolic resin A, the core layer density is 0.85g / cm 3, the adhesive is phenolic resin B, the thickness of the upper and lower surface layers is 15 mm, the thickness of the core layer is 25 mm, the dislocation height h of the surface layer reorganization unit and the core layer reorganization unit at the bonding interface is 10.0 mm, the average diameter of the fiber bundle of the surface layer reorganization unit is 1.2 mm, and the maximum diameter is 1.5 mm; the average diameter of the fiber bundle of the core layer reorganization unit is 3.0 mm, and the maximum diameter is 3.5 mm. The core layer is located between the upper and lower surface layers to form a sandwich structure. The specific preparation method is as follows:

[0184] (1) Synthesis of phenolic resin A and phenolic resin B

[0185] Synthesis of phenolic resin A: 100 parts of phenol, 150 parts of formaldehyde aqueous solution, 5 parts of catalyst (potassium hydroxide) and 4 parts of auxiliary agent (ethylene urea) were weighed by weight, and then the phenol and formaldehyde aqueous solution were added into an autoclave, and the catalyst was added, and the temperature was raised to 80° C. and kept warm for 3 hours. After the heat preservation was completed, the temperature was lowered to 60° C., and the auxiliary agent was added. The temperature was kept warm for 60 minutes, and the temperature was cooled to below 30° C. to obtain phenolic resin A. The prepared phenolic resin A had a viscosity of 140 cps, a solid content of 55%, a pH value of 9.65, and a gel time of 11.6 min at 130° C.;

[0186] Synthesis of phenolic resin B: 100 parts of phenol, 160 parts of formaldehyde aqueous solution, 4 parts of catalyst A (calcium hydroxide, barium oxide, and barium hydroxide in a mass ratio of 1:1:1), 10 parts of catalyst B (potassium hydroxide), 3 parts of carbonate (potassium carbonate and potassium bicarbonate in a mass ratio of 1:1), 30 parts of resorcinol, and 1 part of auxiliary agent (thiourea) were weighed by weight, and then resorcinol, catalyst A, and part of the formaldehyde aqueous solution (10 parts) were added to a reactor, and the temperature was raised to 70° C. and kept warm for 2 hours to obtain a pre-reaction liquid C, and phenol, The remaining formaldehyde aqueous solution was added to another reaction kettle (150 parts), and the catalyst B was added, and the temperature was raised to 80° C. and kept warm for 2 hours. After the heat preservation was completed, the temperature was lowered to 35° C., and the prepared pre-reaction solution C was added, and the temperature was raised to 40° C. and kept warm for 2 hours. After the heat preservation was completed, carbonate and auxiliary agents were added, and the temperature was kept warm for 30 minutes. The phenolic resin B was obtained. The viscosity of the prepared phenolic resin B was 90 cps, the solid content was 50%, the pH value was 9.80, and the gel time at 130° C. was 10.0 min;

[0187] (2) Preparation of recombinant units

[0188] Preparation of surface recombinant units: Rubber wood is decomposed into wood recombinant units with an average fiber bundle diameter of 1.2 mm and a maximum fiber bundle diameter of 1.5 mm using a special decomposition device;

[0189] Preparation of core layer recombinant unit: Rubber wood is decomposed into wood recombinant units with an average fiber bundle diameter of 3.0 mm and a maximum fiber bundle diameter of 3.5 mm by using a special decomposition device;

[0190] (3) Primary drying of the reorganization unit

[0191] The prepared surface layer recombinant unit is dried by a drying device until the moisture content is 8.0% and the drying temperature is 110°C; the prepared core layer recombinant unit is dried by a drying device until the moisture content is 8.0% and the drying temperature is 110°C;

[0192] (4) Recombination unit sizing

[0193] The surface layer reorganization unit after the primary drying is impregnated with phenolic resin, and the sizing amount is 10%; the core layer reorganization unit after the primary drying is impregnated with phenolic resin, and the sizing amount is 10%;

[0194] (5) Secondary drying of the recombination unit

[0195] The pre-impregnated surface layer reorganization unit prepared in step (4) is dried by a drying device to a moisture content of 20% at a drying temperature of 65° C.; the pre-impregnated core layer reorganization unit prepared in step (4) is dried by a drying device to a moisture content of 8% at a drying temperature of 65° C.;

[0196] (6) Recombination unit balance processing

[0197] The surface reorganization units after secondary drying are subjected to balancing treatment in a balancing room until the moisture content is 20%, and the moisture content deviation between the surface reorganization units is controlled within 5%;

[0198] The core layer reorganization unit after secondary drying is subjected to balancing treatment in a balancing room until the moisture content is 8%, and the moisture content deviation between the core layer reorganization units is controlled within 5%;

[0199] (7) Recombination unit assembly

[0200] The mass ratio of the surface layer recombinant unit to the core layer recombinant unit is 1.75;

[0201] The secondary dried surface reorganization unit is evenly divided into two parts, one of which is laid flat on the laying table along the grain as the lower surface layer, and the secondary dried core layer reorganization unit is laid flat on the lower surface layer reorganization unit along the grain, and then the other secondary dried surface layer reorganization unit is laid flat on the core layer reorganization unit along the grain to complete the assembly;

[0202] (8) Hot pressing of reconstituted materials

[0203] The laid reconstructed material slab is sent into a hot press for hot pressing molding. The molding process is as follows: hot pressing temperature 140°C, hot pressing time 90 minutes, hot pressing pressure 8MPa, and a new type of rubber wood reconstructed material can be obtained.

[0204] Test of the Optimum Curing Temperature of Phenolic Resin

[0205] Using a differential scanning calorimeter, the exothermic curves of the phenolic resin A and phenolic resin B synthesized in Examples 1-3 at different heating rates (5°C / min, 10°C / min, 15°C / min, 20°C / min) were tested respectively. According to the peak temperature of the exothermic peak, the heating curve and the peak temperature were linearly fitted by extrapolation to obtain the optimal curing temperature of the resin. The results are shown in Table 2.

[0206] Table 2 Optimal curing temperature for preparing phenolic resin in Examples 1 to 4

[0207]

[0208] It can be concluded from Table 2 that the curing temperature of phenolic resin B is significantly lower than that of phenolic resin A, indicating that phenolic resin B is a low-temperature curing resin.

[0209] The performance of the novel bamboo reconstituted materials prepared in Examples 1 to 4 was tested. The test results are shown in Table 3. The test methods are the same as above.

[0210] Table 3 Performance of recombinant materials prepared in Examples 1 to 4

[0211]

[0212] It can be seen from Table 3 that the physical and mechanical properties of the reconstructed materials prepared in Examples 1 to 4 can all meet the physical and mechanical performance indicators of "Reconstructed Bamboo Flooring" GB / T 30364-2013.

[0213] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A novel recombinant material, characterized in that: It comprises a surface layer and a core layer, wherein the core layer is located between two surface layers to form a sandwich structure; The thickness of the surface layer is 15-40% of the thickness of the novel recombinant material, and the thickness of the core layer is 30-70% of the thickness of the novel recombinant material; The adhesive of the surface layer is phenolic resin A, and the adhesive of the core layer is phenolic resin B; The phenolic resin A uses formaldehyde and phenol as co-condensation raw materials; The phenolic resin B uses phenol, resorcinol and formaldehyde as co-condensation raw materials and carbonate as a modifier.

2. The novel recombinant material according to claim 1, characterized in that: The phenolic resin B comprises the following raw materials in parts by weight: 100 parts of phenol, 120-160 parts of formaldehyde aqueous solution, 2-4 parts of catalyst A, 7-10 parts of catalyst B, 3-6 parts of carbonate, 10-30 parts of resorcinol and 1-5 parts of auxiliary agent.

3. The novel recombinant material according to claim 2, characterized in that: The catalyst A is one or more of calcium oxide, calcium hydroxide, barium oxide, barium hydroxide, zinc oxide or zinc hydroxide; The catalyst B is sodium hydroxide and / or potassium hydroxide; The carbonate is one or more of sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate; The auxiliary agent is one or more of urea, ethylene urea, thiourea or dicyandiamide.

4. The novel recombinant material according to claim 2 or 3, characterized in that: The preparation method of the phenolic resin B comprises the following steps: Weigh the raw materials by weight, then mix resorcinol, catalyst A and part of the formaldehyde aqueous solution, heat and keep it warm to obtain a pre-reaction liquid C, mix phenol, the remaining formaldehyde aqueous solution and catalyst B, heat and keep it warm, cool down after the insulation is completed, add the pre-reaction liquid C, heat and keep it warm, add carbonate and auxiliary agent after the insulation is completed, continue to keep warm, and then cool down to below 30° C. to obtain the phenolic resin B; The molar ratio of formaldehyde to resorcinol in the pre-reaction solution C is 0.5-1.

0.

5. The novel recombinant material according to claim 1, characterized in that: The phenolic resin A comprises the following raw materials in parts by weight: 100 parts of phenol, 110-150 parts of formaldehyde aqueous solution, 5-8 parts of catalyst and 1-4 parts of auxiliary agent; The catalyst is sodium hydroxide and / or potassium hydroxide; The auxiliary agent is one or more of urea, ethylene urea, thiourea or dicyandiamide.

6. The novel recombinant material according to claim 1, characterized in that: The density of the surface layer of the novel recombinant material is 1.15-1.35 g / cm 3 The density of the core layer in the novel recombinant material is 0.65-1.25 g / cm 3 .

7. A method for preparing the novel recombinant material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The surface layer recombinant unit is impregnated or rolled with phenolic resin A to obtain a sizing surface layer recombinant unit, and the core layer recombinant unit is impregnated or rolled with phenolic resin B to obtain a sizing core layer recombinant unit. The sizing surface layer recombinant unit and the sizing core layer recombinant unit are dried, assembled, and hot-pressed to obtain the novel recombinant material.

8. The method for preparing the novel recombinant material according to claim 7, characterized in that: The sizing amount of the phenolic resin A in the surface layer reorganization unit is 8-25%, the sizing amount of the phenolic resin B in the core layer reorganization unit is 5-20%, and the sizing amount of the surface layer reorganization unit is greater than that of the core layer reorganization unit; The average diameter of the fiber bundle of the surface layer reorganization unit is ≤2.5mm, and the maximum diameter is ≤3.0mm; the average diameter of the fiber bundle of the core layer reorganization unit is ≤3.5mm, and the maximum diameter is ≤4.5mm.

9. The method for preparing the novel recombinant material according to claim 7, characterized in that: During assembly, the mass ratio of the glue surface layer recombinant unit to the glue core layer recombinant unit is 1:2-2:

1.

10. The method for preparing the novel recombinant material according to claim 7, characterized in that: The hot pressing temperature is 120-140° C., the hot pressing time is 30-150 min, and the hot pressing pressure is 5-15 MPa.